AP-1 Recruits SMAP-1/SMAPs to the trans-Golgi Network to Promote Sorting in Polarized Epithelia - Wang, Shimin; Yao, Longfeng; Zhang, Wenjuan; Cheng, Zihang; Hu, Can; Liu, Hang; Yan, Yanling; Shi, Anbing (Frontiers in Cell and Developmental Biology, 2021)
Coordinated AP-1 and clathrin coat assembly mediate secretory sorting on the trans-Golgi network (TGN) during conventional secretion. Here we found that SMAP-1/SMAPs deficiency caused the apical protein ERM-1 to accumulate on the basolateral side of the TGN. In contrast, the basolateral protein SLCF-1 appeared abnormally on the apical membrane. SMAP-1 colocalized with AP-1 on the TGN. The integrity of AP-1 is required for the subcellular presence of SMAP-1. Moreover, we found that the loss of SMAP-1 reduced clathrin-positive structures in the cytosol, suggesting that SMAP-1 has a regulatory role in clathrin assembly on the TGN. Functional experiments showed that overexpressing clathrin effectively alleviated exocytic defects due to the lack of SMAP-1, corroborating the role of SMAP-1 in promoting the assembly of clathrin on the TGN. Together, our results suggested that the AP-1 complex regulates the TGN localization of SMAP-1, promoting clathrin assembly to ensure polarized conventional secretion in C. elegans intestinal epithelia.